CODE-MIXING AND CODE-SWITCHING UTTERED BY CINTA LAURA IN OKAY BOSS TRANS7’S TALK SHOW - Yulius Nahak; Barli Bram (UIBU, 2022)
Code-mixing and code-switching can effectively deal with the complex communicative demands that arise when participants have varied levels of linguistic ability. This paper aimed to examine the types and the functions of code-mixing and code-switching uttered by Cinta Laura Kiehl in Okay Boss Trans7’s Talk Show on 23/06/2020, entitled “Ada Apa Dengan Cinta Laura Kiehl dan Aero'' (What happened to Cinta Laura Kiehl and Aero). The design of this study used a qualitative descriptive method. Data were gathered from the talk show in written data. An explanatory sample was used to analyze the collected data. The findings revealed 27 data of code-mixing used by Cinta Laura Kiehl: 19 were intra-sentential code-mixing, and eight were intra-lexical code-mixing. Besides, 19 data of code-switching were identified: 10 were intra-sentential switching, eight were inter-sentential switching, and one was emblematic code-switching. Furthermore, the most dominant function of code-mixing was incompetence, with 15 data, and the most dominant function of code-switching was covering the ability to speak a specific language, with eight data. The study results are expected to contribute to students and lecturers of English and researchers engaging in sociolinguistic research to explore further the purpose of using code-mixing and code-switching in conversation.